2004
DOI: 10.1002/app.20619
|View full text |Cite
|
Sign up to set email alerts
|

CO2‐assisted polymer processing: A new alternative for intractable polymers

Abstract: CO 2 -assisted polymer processing is proposed as an alternative route for intractable and high molecular weight polymers based on the plasticization effects of CO 2 and its direct effect on the melting behavior of semicrystalline polymers. A modified processing system was used to process a variety of polymers in the presence of high-pressure CO 2 . The system includes an extruder that was modified to allow for high pressures created by the injection of CO 2 . The new design includes a modified feed section tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 35 publications
1
28
0
Order By: Relevance
“…Strauss and D'Souza [69] showed for a PS/CO 2 system that the condition δ 1 -δ 2 < 1 required to ensure good gas solubility, would require a saturation pressure of 90MPa at 80°C. However, many studies show that CO 2 molecules are partially soluble in polystyrene matrix (more than 13 wt% with saturation pressures lower than 20 MPa [70,71]). This is because the model does not take into account the specific chemical interactions.…”
Section: Theory On Polymer/co 2 Interactions and Co 2 -Philic Polymersmentioning
confidence: 99%
“…Strauss and D'Souza [69] showed for a PS/CO 2 system that the condition δ 1 -δ 2 < 1 required to ensure good gas solubility, would require a saturation pressure of 90MPa at 80°C. However, many studies show that CO 2 molecules are partially soluble in polystyrene matrix (more than 13 wt% with saturation pressures lower than 20 MPa [70,71]). This is because the model does not take into account the specific chemical interactions.…”
Section: Theory On Polymer/co 2 Interactions and Co 2 -Philic Polymersmentioning
confidence: 99%
“…Previous research using scCO 2 to facilitate processing resulted in foams [30,31]. In the present work, a slow vent rate was used to minimize pore generation.…”
Section: Density Measurementsmentioning
confidence: 99%
“…These concepts can be utilized in the fabrication of PLS nanocomposites as a few authors have reported. 213,214 However, the extent of success is questionable and further research is needed because most authors did not investigate or report quantitatively the improvements in the materials' properties.…”
Section: Nanocomposite Synthesis With the Aid Of Sc-comentioning
confidence: 99%